(untitled) (Archaeologia Adriatica, 2025)
In the extensive body of diversely worked, widely distributed and quantitatively extremely well-represented Certosa-type fibulae, Certosa Ic- and Id-type fibulae have long been identified as chronologically younger variants, autochthonous of the territories occupied by the Liburnians and Iapodians. Their number has significantly increased following recent systematic excavations of the flat necropolis in Nadin, in which 42 specimens were recovered. Together with the two previously published fibulae from Tomb 1 at Nadin, their total volume there exceeds 40 per cent of the entire known body of Certosa Ic- and Id-type fibulae. The article discusses the Nadin fibulae, comparing them with others of this type, in particular dealing with their possible typological and chronological classification. Regarding the typological variability of the Nadin specimens, the introduction of a new variant – of undecorated bow (Ie), with three sub-variants (Ie1, Ie2 and Ie3) – is proposed. At the same time, the conclusion of the use of the Certosa Ic-, Id- and Ie-type fibulae is to be dated slightly later than previously assumed, to (at least) the first half of the 1st century BC.